Motivation Of Deaf Students Towards Sports Learning At SLB B Tunas Harapan Karawang - Saleh, Muhammad Fakhri; Winarya, Fazri Ramdhani; Ramadhani, Fatiha; Setiawan, M. Arief (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aims to explore the level of learning motivation of deaf students towards sports learning at SLB B Tunas Harapan, Karawang. By using quantitative descriptive, and collecting information or data using surveys. This study involved 10 students of SLB B Tunas Harapan as a population, which was taken through random sampling techniques. Data were collected using questionnaires designed to measure students' learning motivation in the context of physical education or sports. The results of the analysis show that the level of student motivation in sports learning is in a good category, with the percentage of motivation reaching 60%. These findings indicate that although deaf students show interest in learning sports, there is a need to improve teaching strategies to make them more engaging and enjoyable. Therefore, it is recommended that teachers apply interactive and game-based learning methods to increase student engagement so that they do not feel bored and are more motivated to follow lessons. This research is expected to provide insight for educators and schools in designing more effective learning programs for deaf students, as well as supporting the development of their potential in the field of sports. This abstract provides a comprehensive overview of the objectives, methods, results, and implications of research on the learning motivation of deaf students at SLB B Tunas Harapan Karawang.